Accidental Poisoning among Children’s Less than Five Years old in Baqubah City - Ali, Sabah Mohsin (Diyala Journal of Medicine, 2019)
Background: Poisoning among children less than 5 years remain as major public health Problem worldwide despite improving in health services. Objective: To find out the causes of poisoning between children less than 5 years old in Baqubah City according to type of poisons, age, address, gender, socioeconomic status and education of parents. Patient and Method: Cross sectional study describes poisoning among children less than5 years old admitted to the Al- Batool Teaching Hospital for period from the 1st July 2014 to the1st April 2015. Result: One hundred twenty five children less than 5 years old were admitted to Al- Batool Teaching Hospital due to an accidental poisoning. Hydrocarbons were the most common cause of Poisoning (82), (65.60%), drugs (34), (27.20%), organophosphorous (5), (4, 0%), and corrosive (4), (3.20%) .The majority of children were (1 -3) years of age (72), (57.6%).Male (77), (61.6%) female (48), (38.4%) male : female ratio (1.6:1). Address distribution, rural (76), (60.8%) urban (49), (39.2%). Socioeconomic status, low socioeconomic status (109), (87.2%) intermediate socioeconomic status (16), (12.8%). Father Education: primary education (65), (52.0%), secondary (56), (44.8%) and graduated (4), (3.2%). Education of mother primary (91), (72.8%) and secondary (33), (27.2%). Conclusion: Majority of the poisonings in children were due to ingestions of poisons among age group (1-3) years, with male gender predilection, Hydrocarbon was the most commonly ingested poisoning agents; Patients parent both had low socioeconomic status and low educational level.